Retreatment Strategies for Cases Containing Calcium Silicate-Based Root Canal Sealers: A Comprehensive Review - Hussain Al akam; Hyeon-Cheol Kim; Ji Wook Jeong (MDPI AG, 2024)
This review explores the field of retreatment strategies for cases filled with calcium silicate-based root canal sealers. Since the introduction of calcium silicate-based materials in dentistry, calcium silicate-based root canal sealers have become popular among dentists because of their biocompatibility, bioactivity, and sealing ability. Therefore, effective retreatment strategies are indispensable. This article aims to identify the challenges associated with the removal of calcium silicate-based sealers themselves and removal of gutta-percha with the sealers during retreatment, evaluate current techniques and materials, and provide future directions for research in this field. Regarding the strategies of removal of root canal sealers, calcium silicate-based sealers are still relatively new materials for clinicians compared with traditional sealers such as epoxy- or eugenol-based sealers. First, no clinically established solvents have been reported. Second, calcium silicate-based sealers are currently utilized by clinicians in either the cold sealer-based technique or the warm vertical condensation technique. Third, the setting process of calcium silicate-based sealers generates byproducts, primarily calcium hydroxide and secondarily hydroxyapatite, that could interact with dentine. Lastly, there is a lack of clinical studies evaluating the efficacy of retreatment protocols for teeth filled with calcium silicate-based sealers. Therefore, it is important to investigate the chemo-mechanical properties of calcium silicate-based sealers themselves and their reactions to solvents and/or mechanical instruments and identify the interfacial properties of calcium silicate-based sealers with respect to dentine and gutta-percha. In addition, researchers in the clinical field need to actively gather and report data on retreatments of teeth filled with calcium silicate-based sealers.